Experimental stand and testing method for a metal-wood I-beam (Far Eastern Federal University: School of Engineering Bulletin, 2024)
The rational distribution of materials in combined structures makes them more profitable in comparison with the classic versions of beams made of rolled or laminated wood. In this work, the authors consider the rationale for an experimental stand that can be used to study the stress-strain state of metal-wood I-beams with a wall made of prefabricated profiled sheet. The general design of the stand, materials and devices necessary for carrying out the experimental study are presented.